2006
DOI: 10.1007/s11075-006-9020-z
|View full text |Cite
|
Sign up to set email alerts
|

On a nonlinear multigrid algorithm with primal relaxation for the image total variation minimisation

Abstract: Digital image restoration has drawn much attention in the recent years and a lot of research has been done on effective variational partial differential equation models and their theoretical studies. However there remains an urgent need to develop fast and robust iterative solvers, as the underlying problem sizes are large. This paper proposes a fast multigrid method using primal relaxations. The basic primal relaxation is known to get stuck at a Flocal_ non-stationary minimum of the solution, which is usually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 34 publications
0
35
0
Order By: Relevance
“…The answer is no, if the functional J is non-smooth. However, in [7], we found that the wrongly converged solution is only incorrect near flat patches of the solution. The idea of detecting such flat patches during iteration and incorporating new local minimizations based on the patches was suggested in [7].…”
Section: Review Of a Multilevel Methods For Optimizationmentioning
confidence: 81%
See 4 more Smart Citations
“…The answer is no, if the functional J is non-smooth. However, in [7], we found that the wrongly converged solution is only incorrect near flat patches of the solution. The idea of detecting such flat patches during iteration and incorporating new local minimizations based on the patches was suggested in [7].…”
Section: Review Of a Multilevel Methods For Optimizationmentioning
confidence: 81%
“…We now briefly review the multilevel method proposed in [7] for removing Gaussian noise. One nice advantage about the method is that it can be applied to non-smooth functionals as it does not require their derivatives.…”
Section: Review Of a Multilevel Methods For Optimizationmentioning
confidence: 99%
See 3 more Smart Citations